Case study research : a theoretical overview, systematic review & analytical examination regarding Rosenzweig's delusions - Hüller, Maximilian (2015)
This master’s thesis will introduce the case study method from various perspectives. In order to carry out a systematic review and an analytical examination regarding Rosenzweig’s delusion the paper provides firstly a comprehensive introduction about the case study method from a theoretical viewpoint. In this context the current opinion, challenges, and available designs are reflected in great detail. By doing so a knowledgeable foundation is created, as several renowned researchers’ concepts and opinions are inte- grated. The theoretical chapter demonstrates various developments of the case study method, which have promoted this scientific approach. The focus of this paper lies on analysing case studies, which were published between the years of 1995 and 2009 in five selected management journals. By using the method of a systematic review, case studies are examined extensively regarding their general and thematic contributions. The main objective is particularly to provide a broad knowledge- base on the basis of the articles’ contributions. Hereby, the 120 identified articles are firstly introduced from a descriptive perspective, which allows to report about general in- formation. Afterwards 75 of the 120 studies, which show clear attributes of real case stud- ies, are analysed thematically. The second research objective is to investigate representative case studies from the 75 articles including sample whether they are affected by Rosenzweig’s delusions. In this context the articles will be analysed in terms of four delusions, which are especially re- lated to the case study method. This analytical analysis aims to illustrate how the re- searchers addressed issues related to the quality of the used data or the Halo Effect. In total the analysis illustrated the distribution of the articles over the years and across the journals. Moreover, it was reported which industries, countries, and topics were examined in the context of the sample. Whereas a clear focus on certain countries could be re- ported, it could not be observed in terms of the investigated topics, as those were covered equally across the journals. The analytical analysis about the potential containment of delusions illustrated that the studies often rely on data sources such as interviews or journal articles, which tend to include the Halo Effect. However, the required scientific quality regarding the overall data is warranted by using the triangulation approach. These sources are significant for the case study method in order to gain deep insights, as no other method is able to achieve this properly and therefore their use is necessary.